Aspects of The Character Binta’s Personality in The Novel Kata by Rintik Sedu: Sigmund Freud’s Psycoanalytic Study - Eva Yulianti; Yundi Fitrah; Nurfadilah (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research aims to describe the personality aspects of the character Binta in the novel Kata by Rintik Sedu which includes Id, Ego, Superego. The formulation of the problem in this research is what aspects of the character Binta's personality in the novel Kata by Rintik Sedu include Id, Ego, Superego. This research uses qualitative methods and descriptive research. The data source for this research is the novel Kata by Rintik Sedu. The data in this research is in the form of the behavior or actions of the character Binta as depicted in dialogue or narration in the novel Kata by Rintik Sedu. The results of the research show that in the novel Kata by Rintik Sedu there is a personality structure of the character Binta which is viewed from the psychoanalytic aspect of Sigmund Freud. These personality aspects can be classified into three, namely: id, ego, and superego. The novel Kata by Rintik Sedu can be used as a breakthrough as an alternative teaching material which aims to improve students' ability to appreciate in analyzing the psychology of story characters from a literary work.